2019
DOI: 10.5585/riae.v18i4.10971
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national distance impact on FDI strategic decisions into Portugal: Evidence from Eurozone and Ibero-America

Abstract: Purpose: The purpose of this paper is to assess if MNEs from the Eurozone and Ibero-America have different sensitivities to cross-national distance when investing in Portugal, by comparison with non-Eurozone and non Ibero-American MNEs.Methodology: Using qualitative variables on a panel data analysis, we are able to assess the differentiated effects of cross-national distance on MNEs from members and non-members of both groups of countries.Findings: Results suggest that sensitivities are indeed differentiated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, it is observed that economic distance (measured by market size) promotes FDI inflows. In this line, the study by Duarte and Carvalho (2019) carried out for FDI inflows from Eurozone and Ibero-American countries from 2003 to 2015 demonstrated that the economic dimension and geographical proximity measured by the border have a more significant impact on the Portuguese FDI.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Furthermore, it is observed that economic distance (measured by market size) promotes FDI inflows. In this line, the study by Duarte and Carvalho (2019) carried out for FDI inflows from Eurozone and Ibero-American countries from 2003 to 2015 demonstrated that the economic dimension and geographical proximity measured by the border have a more significant impact on the Portuguese FDI.…”
Section: Literature Reviewmentioning
confidence: 96%